The phytochemical properties, pharmacological effects and traditional uses of Actinidia eriantha Benth.: A review - Wang, Shiyu; Gao, Xiaoqi; Sun, Qingmei; Zhu, Yichun; Qin, Luping; Zhu, Bo (Frontiers in Pharmacology, 2022)
Actinidia eriantha Benth. (Called Maohuamihoutao in China) is a plant that has been utilized as a heat-clearing drug in She ethnic minority group for a long time in China. Specifically, it has been involved in the treatment of stomach cancer, colon cancer, cirrhosis with ascites, chronic hepatitis, leukemia, rectal prolapse, hernia and uterine prolapse. Pharmacological research provides partial evidence for the traditional use of A. eriantha and might have demonstrated the folk utilization of A. eriantha to combat many cancers. Crude extracts and relatively pure components of A. eriantha possess a variety of pharmacological activities, including anti-cancer, immunoregulatory, anti-angiogenic, neuroprotective, anti-inflammatory, and antioxidant activities. In addition, over 104 chemical substances have been determined from A. eriantha, involving terpenoids, alcohols, phenolics, aldehydes, organic acids, flavonoids glycosides, ketones, and glucoside. The existing literature reveals that a large proportion of the therapeutic effects of A. eriantha were rendered by the polysaccharides. However, the mechanisms of action and the structure-function correlations of these compounds, as well as the synergistic and antagonistic effects between them, need to be investigated further. Therefore, we propose that future studies on A. eriantha should focus on comprehensively assessing its medicinal quality, exploring its multi-target nature using network pharmacology approaches, and evaluating its long-term toxicity and efficacy in vivo.